Mutation analysis of patients with neurodegenerative disorders using NeuroX array - Ghani, Mahdi (2015)
Genetic analyses of patients with neurodegenerative disorders have identified multiple genes that need to be investigated for the presence of damaging variants. However, mutation analysis by Sanger sequencing is costly and time consuming. We tested the utility of a recently designed semi-custom genome-wide array (NeuroX; Illumina, Inc) tailored to study neurodegenerative diseases (e.g., mutation screening). We investigated 192 patients with 4 different neurodegenerative disorders for the presence of rare damaging variations in 77 genes implicated in these diseases. Several causative mutations were identified and confirmed by Sanger sequencing, including PSEN1 p.M233T responsible for Alzheimer's disease in a large Italian family, as well as SOD1 p.A4V and p.I113T in patients with amyotrophic lateral sclerosis. In total, we identified 78 potentially damaging rare variants (frequency <1%), including ABCA7 p.L400V in a family with Alzheimer's disease and LRRK2 p.R1514Q in 6 of 98 patients with Parkinson's disease (6.1%). In conclusion, NeuroX appears to be helpful for rapid and accurate mutation screening, although further development may be still required to improve some current caveats.